A cross sectional study of association of anaemia with BMI in medical and paramedical students - Agarwal, Ajay Kumar; Katiyar, Ghanshyam Das; Mahmood, Syed Esam; Khan, Swati; Sharma, Mahendra (International Journal Of Community Medicine And Public Health, 2017)
Background: Anaemia is a global health problem. Anaemia is one of most commonly recognized disorders. In view of ever increasing burden of anaemia in India and its detrimental effects on academic performance of students, it is necessary to find out the association of anaemia with BMI of medical and para medical students. This study was undertaken to find out association of anaemia with BMI among medical and para medical students of Rohilkhand Medical College, Bareilly. Methods: This cross sectional study was conducted in 344 medical and para medical students of Rohilkhand Medical College and Hospital, Bareilly. A structured schedule was used to collect the information regarding anaemia and BMI. Data was analyzed using SPSS software. Chi square test was applied. Results: Over all prevalence of anaemia was 29.07% prevalence was higher among female students (41.92%), among those aged between 25-26 years (75.00%) and among Muslims (40.54%), prevalence of anaemia among normal weight (31.92%) followed by underweight (27.02%) than in preobese (25.86%) while least among obese (20.83%). Conclusions: Anaemia is prevalent even in medical and para medical students who are well educated and well oriented about nutrition and its ill effect on health. BMI exhibits higher prevalence of anaemia among normal weight, followed by underweight, preobese and obese.